Management of Surgical Wound Care Using the Bundles Principle as an Infection Control Strategy in Post-operative Patients - Lestari, Sri; Pratiwi, Arum; Alis Setiyadi, Noor (Poltekkes Kemenkes Surakarta, 2024)
Background: Infection prevention strategies, such as applying the bundle's principle, play a vital role in surgical wound care. However, limited studies assess nurse compliance with these standards. Investigating compliance is crucial to understanding its impact on post-operative wound infection. This study examines how nurse adherence to the bundle's principle influences wound infection during the healing process. Methods: A before-and-after study was conducted at a second-level hospital in Indonesia over three months. Using total sampling, 100 nurses meeting inclusion criteria (adults with over one year of experience and training in bundle strategies) participated. Patients were selected through accidental sampling and included adults with non-infectious surgical wounds and no complications. The bundle's principle was implemented from the third to the sixth postoperative day, with infection signs assessed afterward. Instruments included demographic data, compliance checklists, and wound infection assessments. Data were analyzed using logistic regression. Results: Gender did not significantly affect wound infection occurrence (OR 0.39, *P* = 0.092). Nurse compliance and work length showed a significant association with infection prevention (OR 4.47, *P* = 0.006). Educational background was not significantly associated with compliance (OR 2.11, *P* = 0.409). Conclusion: Nurses' compliance with the bundle's principle significantly reduces post-operative wound infections, promoting effective healing. Factors like gender, work length, and educational background contribute equally to post-operative wound care outcomes.